A BRIEF STUDY ON THE LIFE SKILLS EDUCATION - ANJLI DANGI; DR. PRAMILA MALIK (Innovative Research Thoughts, 2023)
Basic skills academic achievement is intended to facilitate the ability for ppl to train and reinforce experience in mind in a manner that seems to be culturally specific in addition to appropriate behavior in so as to encourage emotional and social progression, avoid physical and social matters, and protect human rights. This is done in order to prevent social and medical issues from occurring. If correctly acquired, life skills, along with other functional talents, have the potential to aid individuals in better comprehending how they feel about themselves and how they regard others. These capabilities educate nous on how to interact effectively with ourselves as well as others, which enables nous to sidestep a great deal of needless conflict or difficulty that nous impose on ourselves. They also assist us in living our lives in an organised manner. In a word, life skills are marketable abilities that are aimed to offer learners with new and enhanced competencies, capacities, and positive behavioural changes. The term life skills refers to a person's capacity for adaptability and good behaviour, which enables them to effectively deal with the demands and challenges that are a part of everyday life. Life skills are defined as the abilities to behave in a way that is adaptable and productive. Having life skills means having the ability to take care of one's mental and bodily well-being while also interacting with the people and the traditions of one's surrounds and culture.